Prevalência e caracterização de amostras de Escherichia coli diarreiogênica isoladas de crianças na cidade de Botucatu, São Paulo - Dias, Regiane Chrysostomo Bitencort [UNESP] (2015)
Diarrheagenic Escherichia coli (DEC) comprises a major cause of child hood diarrhea. Based on their virulence mechanisms, DEC can be classified into six distinct pathotypes: enteropathogenic E. coli (EPEC), enterotoxigenic E. coli (ETEC), enteroinvasive E. coli (EIEC), enteroaggregative E. coli (EAEC), enterohemorrhagic E. coli (EHEC) and diffusely adherent E. coli (DAEC). This study aims to investigate the prevalence of DEC among diarrheal children (patients) and healthy children (controls), up to five years of age in Botucatu/SP. We analyzed stool samples from 200 children with diarrhea attended at Hospital das Clínicas da Faculdade de Medicina de Botucatu, between March/2013 and September/2014, and 200 healthy children. E. coli isolates were classified in different pathotypes by detection of virulence markers (by PCR) and then, characterized regarding its adherence pattern to HeLa cells and antimicrobial resistance drugs. Isolates carrying the locus of enterocyte effacement (eae+) were submitted to FAS test (Fluorescence Actin Staining), to evaluate the ability of these isolates to induce attaching and effacing lesion (AE). In addition, EPEC and STEC isolates, had their somatic (O) and flagellar (H) antigens determined. DEC was isolated from 18.0% of diarrheal children, and 19.0% of healthy children, and none of the DEC pathotypes could be individually associated with the diarrheal disease (P>0.05). EAEC was the most frequent DEC pathotype, being detected in equal proportion between patients and controls (10.0%). Among the EPEC isolates, 16 from patients and 18 from controls, only one was able to produce the localized adherence (LA) pattern to HeLa cells, being this isolate the only typical EPEC (tEPEC) identified in this study. The remains EPEC isolates were classified as aEPEC (atypical EPEC), and detected in 8.0 and 8.5% of the patients and controls, respectively. STEC and ETEC were detected in only one child from each studied ...